Ответ:
в)
г)
Пошаговое объяснение:
1 . в ) ( a² + 1 )/2a = a²/2a + 1/2a = a/2 + 1/2a ;
г ) ( a² - 3ab )/a³ = a²/a³ - 3ab/a³ = 1/a - 3b/a² .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
в)![\frac{a^2}{2a} + \frac{1}{2a} = \frac{a}{2} + \frac{1}{2a} \frac{a^2}{2a} + \frac{1}{2a} = \frac{a}{2} + \frac{1}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E2%7D%7B2a%7D%20%2B%20%5Cfrac%7B1%7D%7B2a%7D%20%3D%20%5Cfrac%7Ba%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B2a%7D)
г)![\frac{a^2}{a^3} - \frac{3ab}{a^3} = \frac{1}{a} - \frac{3b}{a^2} \frac{a^2}{a^3} - \frac{3ab}{a^3} = \frac{1}{a} - \frac{3b}{a^2}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E2%7D%7Ba%5E3%7D%20-%20%5Cfrac%7B3ab%7D%7Ba%5E3%7D%20%3D%20%5Cfrac%7B1%7D%7Ba%7D%20-%20%5Cfrac%7B3b%7D%7Ba%5E2%7D)
Ответ:
Пошаговое объяснение:
1 . в ) ( a² + 1 )/2a = a²/2a + 1/2a = a/2 + 1/2a ;
г ) ( a² - 3ab )/a³ = a²/a³ - 3ab/a³ = 1/a - 3b/a² .